Tillage and Previous Crop Effects on Dynamics of Nitrogen in a Wheat–Soil System - Soon, Yoong Kee; Clayton, George W.; Rice, Wendell A. (Agronomy Journal, 2001)
The effects of tillage and preceding legume crops on N flux in the soil–plant system require quantification for developing sustainable cropping systems. We measured changes in soil and plant N under the influence of tillage [no till (NT) vs. conventional tillage (CT)] and previous crops [spring wheat ( Triticum aestivum L.), red clover ( Trifolium pratense L.) green manure, and field pea ( Pisum sativum L.)]. The study was conducted from 1994 through 1996 on a well‐drained sandy loam soil (coarse‐loamy, mixed, frigid, Typic Cryoboralf) near Fort Vermilion, Alberta (58°23′N, 116°2′W). Nitrogen uptake by wheat was increased by NT and legume crops. At seeding, CT soil had 28 kg ha −1 more NO 3 –N to 100‐cm depth than NT soil. Apparent net N mineralization in the growing season was 71 and 22 kg N ha −1 , respectively, for the NT and CT systems. Previous crop effect on net N mineralization (kg N ha −1 ) was red clover (56) > field pea (51) > wheat (34). Approximately 18 kg N ha −1 was net‐mineralized from red clover residues compared with insignificant amounts from pea and wheat residues. Microbial biomass turnover's contribution to net N mineralization (28 to 40 kg N ha −1 ) was increased by NT and previous legume crop. Soluble organic N decreased by 7 kg ha −1 between seeding and maturity for all experimental treatments. The results indicate that N fertilizer recommendations should allow for greater mineralization of organic N under NT than CT and following a legume green manure.